(3OjhGf CHj aQGS GdMeOGfis - (3CHh aQGS , GdMGQK Hf SYjO Hf MeOGf GdJZdHj GdQHYj, CHhaQGS GdMeOGfj,J (B357 (3g` s ((3jMi Hf Ydi Hf GHQGgje Hf GdegOi s)
(3ChdgG (B:s
(3bGd CHh YHO Gddg GdMSjf Hf NGdhjg ef bGajg GdCda Ye UHGMkG hEf ZOhJ NdGA ef XGA jaVMf ajc GdXHGA s
(3BNQgG (B:s
(3ef CQLhRI (B: (3ade fRd SHY djGd YOOkG CSYO ef QGM hCNWi ef ZOG s
(3QhGjI GHf NGdhjg eQJH Ydi GdbhGais
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B156s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs